A Study on Pervious Concrete with Fly Ash Replacement - Lauw, Hong Aik (2017)
The fly ash replacement with o%, 5%, 10%, 15% and 20% will conduct for getting the optimum result of mechanical properties of previous concrete. The mechanical properties were measured like compressive strength, flexural strength, splitting-tensile strength, sieve analysis, porosity and permeability. Besides that, the relationship of the compressive strength versus porosity and permeability versus porosity has been plotted during 28th days. In additional, the method of measured the permeability is used constant head method. This research find out the optimum of fly ash replacement is 5% with the highest of compressive strength and splitting-tensile strength follow by 8.57 MPa and 7Mpa respectively. However, the permeability is 4.34 L/min which fall in the requirement range of 0.67 L/min to 10 L/min.